2011
DOI: 10.1016/j.actamat.2011.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Structure, shear resistance and interaction with point defects of interfaces in Cu–Nb nanocomposites synthesized by severe plastic deformation

Abstract: We use atomistic modeling to investigate the shear resistance and interaction with point defects of a Cu-Nb interface found in nanocomposites synthesized by severe plastic deformation. The shear resistance of this interface is highly anisotropic: in one direction shearing occurs at stresses below 1200MPa while in the other it does not occur at all. The binding energy of vacancies, interstitials, and He impurities to this interface depends sensitively on the binding location, but there is no point defect deloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(80 citation statements)
references
References 59 publications
2
77
0
1
Order By: Relevance
“…When h refines to 50 nm, the amount of the {112}o1114Cu (C)||{112}o1104Nb interface increases and twins form in the Cu layers 35,36 . The two aforementioned interfaces are ordered, containing regular arrays of facets and interfacial dislocations to accommodate the lattice mismatch between the phases [36][37][38] (see Supplementary Fig. S4).…”
Section: Resultsmentioning
confidence: 99%
“…When h refines to 50 nm, the amount of the {112}o1114Cu (C)||{112}o1104Nb interface increases and twins form in the Cu layers 35,36 . The two aforementioned interfaces are ordered, containing regular arrays of facets and interfacial dislocations to accommodate the lattice mismatch between the phases [36][37][38] (see Supplementary Fig. S4).…”
Section: Resultsmentioning
confidence: 99%
“…Cross-element interactions were fitted to reproduce the high positive dilute enthalpies of mixing of Cu in Nb and Nb in Cu as well as the lattice parameter and bulk modulus of a hypothetical Cu-Nb compound in the Cs-Cl structure 43 . This potential has been used in numerous previous studies of the structure and properties of Cu-Nb interfaces 13,16,40,[44][45][46] .…”
Section: Interface Model and Simulation Methodsmentioning
confidence: 99%
“…However, it has been found that the local energetic structure and the local stress state of the GB can not be neglected in the context of dislocation interactions near GBs, in general [103]. Additional considerations include, e.g., the interface shear strength [100][101][102]. In the atomistic simulations [105] and in the combined computational / experimental approaches [28], the importance of the RBV for the slip transmission has been demonstrated.…”
Section: Computational Investigation Of Slip Transmission Criteriamentioning
confidence: 99%